Understanding Infants' In-Home Injuries: Context and Correlates. (20th August 2021) - Morrongiello, Barbara A; Corbett, Michael; Bryant, Lindsay; Cox, Amanda
Abstract: Rationale: Infancy is a time of elevated risk of injury. Past research has focused mostly on the type of injuries, leaving many gaps in knowledge about contextual information that could aid in injury prevention planning. Methods: In this longitudinal study, a participant-event recording method was used in which mothers tracked their infants' home injuries through three motor development stages (sitting up independently, crawling, and walking). A contextual analysis elucidated where injuries occurred, their type and severity, the infant's and parent's behaviors at the time, if the infant had done the risk behavior before and been injured, the level of supervision, and the nature of any safety precautions parents implemented following these injuries. Results: Injuries occurred as often in play as in nonplay areas and were due to physically-active nonplay activities more so than play activities; mothers were often doing chores. Bumps and bruises were the most common types of injuries. As infants became more mobile, supervision scores declined and injury severity scores increased. Infants had done the risk behavior leading to injury previously about 60% of the time, with higher scores associated with parents implementing fewer preventive actions in response to injury. When mothers did implement a safety precaution, greater injury severity was associated with more modifications to the environment and increased supervision; teaching about safety was infrequent. Conclusion: Implications of these results for injury prevention messaging are discussed.